A novel solar and geothermal-based trigeneration system for electricity generation, hydrogen production and cooling. (15th October 2019) - Siddiqui, Osamah; Ishaq, Haris; Dincer, Ibrahim
Highlights: A novel renewable energy based system utilizing solar and geothermal resource. Thermochemical CuCl cycle is integrated for hydrogen production. The overall energy and exergy efficiency of the system is 19.6% and 19.1%. The CuCl cycle energy and exergy efficiency is 35.3% and 35.9% respectively. Abstract: In this study, a novel renewable energy based trigeneration system is developed based on the utilization of solar and geothermal resources in a combined manner. The present system includes the following useful outputs, namely electricity, hydrogen and cooling. A flash-steam geothermal power plant is used for producing electricity. The CuCl cycle is used for hydrogen production and an additional heat from the CuCl cycle is used in the absorption chiller for cooling. The energy efficiency of the trigeneration system is evaluated to be 19.6% while the exergy efficiency is found to be 19.1%. Furthermore, the CuCl hydrogen production cycle is determined to have an energy efficiency of 35.3% and an exergy efficiency of 35.9%. In addition, the energetic coefficient of performance of the absorption cooling system is evaluated as 0.54 and the exergetic coefficient of performance is 0.32. Moreover, several parametric studies are conducted to study the effects of varying operating conditions and system parameters on system performance.